Penerapan Norma Hukum Klausul Baku Dalam Klausul Penarikan Kendaraan Bermotor Pada Perjanjian Pembiayaan Konsumen - Wanda Myra Carissa; Tan Kamello; Hasim Purba; Dedi Harianto (Mahesa Research Center, 2022)
This article aims to consumer financing agreements, standard clauses that have made previously by finance companies are stipulated as fixed requirements and cannot negotiate anymore. In the consumer financing agreement, there is a fiduciary guarantee so that a vehicle withdrawal clause include as a consequence of the breach of contract carried out by the consumer. This vehicle withdrawal clause often creates problems ahead between finance companies and consumers as in the District Court's Decision No. 105/Pdt.G/BPSK/2012/PN.Ska and No. 24/Pdt.G/BPSK/2013/PN.Skw. The problem in this research is about how the legal force of the standard clause in the consumer financing agreement according to the regulations in force in Indonesia, how the legal protection of consumers the application of the vehicle withdrawal clause in the consumer financing agreement and how the legal reasoning of judges in assessing the validity of the vehicle withdrawal clause in a consumer financing agreement (Study of District Court Decisions No. 105/Pdt.G/BPSK/2012/PN.Ska and No. 24/Pdt.G/BPSK/2013/PN.Skw). The research employed normative laws and analytically descriptive. This research also using the statute approach and conceptual approach. Analysis of the data used in legal materials in this research will carry out in a qualitative analysis of primary data and secondary data that describe and analyze the standard clauses and vehicle withdrawal clauses in consumer financing agreements, as well as concluding by deductive method. This study concludes that the legal force of a standard clause in a valid and binding consumer financing agreement applies as a law to the parties as long as it meets formal and material conditions based on Law No.8/1999 concerning Consumer Protection, OJK Regulation No. 1/POJK/07/2013 concerning Consumer Protection in the Financial Services Sector, OJK Circular Letter No.13/SE.OJK.07/2014 concerning Standard Agreement and OJK Regulation No. 35 /POJK.05/2018 concerning Business of a Financing Company. Legal protection for consumers in the application of a vehicle withdrawal clause because of a breach of contract by the consumer is preventive legal protection and repressive legal protection. Legal reasoning for judges in making decisions does not consider the validity of the agreement process in the consumer financing agreement because the vehicle withdrawal clauses listed can categorize as defects in the agreement abuse of circumstances.